2019
DOI: 10.4103/jfmpc.jfmpc_235_19
|View full text |Cite
|
Sign up to set email alerts
|

An audit of the appointment booking system and patient waiting time in an ultrasound unit in Nigeria: A need to eliminate congestion in our public hospitals

Abstract: Background: Congestion of patient waiting areas at commencement of work is the usual scenario in Nigeria's public hospitals. This strains the personnel and facilities. Patients are dissatisfied and lose faith in the system. This study aims to audit the booking system, patient waiting time, and causes of congestion in an ultrasound unit. Materials and Methods: This is a prospective, descriptive study involving 350 patients referred from general outpatient and specialist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…The causes of long waiting time in the present study were associated with ineffectual appointment scheduling, mismatch between patient arrival time, and staff service commencement time/staff inefficiencies, inconsistent power supply, and equipment function-related disruptions. Akintunde et al (2019) identified ineffective scheduling and unpunctuality of sonologists as major causes of congestion in ultrasound units, findings that showed similarity to the present work. To obviate this problem, the researchers made the following recommendations: Changing the appointment system from single block to modified block scheduling, or individual scheduling; ensuring commencement of service to correspond to arrival time of patients; and prioritizing seeing patients and postponing other activities to less busy hours; provision of a dedicated power generating set which will solve the problem of power outage in the unit; ensuring that all the ultrasound machines are functional per time through good quality control practices which will reduce to the barest minimum the contribution of equipment breakdown to patient delays.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The causes of long waiting time in the present study were associated with ineffectual appointment scheduling, mismatch between patient arrival time, and staff service commencement time/staff inefficiencies, inconsistent power supply, and equipment function-related disruptions. Akintunde et al (2019) identified ineffective scheduling and unpunctuality of sonologists as major causes of congestion in ultrasound units, findings that showed similarity to the present work. To obviate this problem, the researchers made the following recommendations: Changing the appointment system from single block to modified block scheduling, or individual scheduling; ensuring commencement of service to correspond to arrival time of patients; and prioritizing seeing patients and postponing other activities to less busy hours; provision of a dedicated power generating set which will solve the problem of power outage in the unit; ensuring that all the ultrasound machines are functional per time through good quality control practices which will reduce to the barest minimum the contribution of equipment breakdown to patient delays.…”
Section: Discussionsupporting
confidence: 88%
“…To obviate this problem, the researchers made the following recommendations: Changing the appointment system from single block to modified block scheduling, or individual scheduling; ensuring commencement of service to correspond to arrival time of patients; and prioritizing seeing patients and postponing other activities to less busy hours; provision of a dedicated power generating set which will solve the problem of power outage in the unit; ensuring that all the ultrasound machines are functional per time through good quality control practices which will reduce to the barest minimum the contribution of equipment breakdown to patient delays. Akintunde et al (2019) suggested modified block scheduling and introduction of point-of-care ultrasound to minimize service bottlenecks and improve patient satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study revealed that the major cause for congestion is the type of appointment scheduling adopted in the unit. The schedule is inconsistent in terms of start time, number of patients per block, and time slots (Akintomide et al, 2019). The congestion varies depending on health facilities and many other factors, such as quality of medical facilities, quantity and quality of medical equipment, the capacity of human resources, and speed of a registration process (Babalola et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…By using the traditional walk-in method where the patient is required to wait in line, the waiting time for patients increases, it overloads the MHF and it is influencing the work on the physician [1]. Additionally, crowded waiting rooms for the patients are a usual thing in the MHF [2]. With the fast improvement of the Internet information technology over the years, many MHF lean towards using electronic appointment systems for patients (EASP) [1].…”
Section: Introductionmentioning
confidence: 99%